Investigating the Characteristics of Freeze-Dried Mucin Extract from Snail Achatina Fulica and Silicone Adhesive Films for the Development of Wound Healing Patches - Zulkifle, Muhammad Aminuddin; A Razak, Aliff Hisyam (Progress in Engineering Application and Technology, 2025)
This study investigates the characterization of freeze-dried snail mucin extract from Achatina Fulica with silicone adhesive film for its potential use in wound healing patches. The research aims to address the problem of current wound healing patches that face limitations such as moisture buildup and adhesive-induced skin irritation, which can compromise patient comfort, delay healing, and reduce overall efficiency. By employing freeze-drying techniques within ethical guidelines, the study seeks to optimize mucin extraction by carefully removing moisture under low temperatures to preserve its bioactive properties. An optimization method was used to identify key factors such as mixing time, curing time and loading of freeze-dried snail mucin that influence adhesiveness and permeability of the patch. The optimized conditions were found to be 10 minutes, 50 minutes, and 5 phr. The silicone encapsulated the snail mucin lacked antimicrobial properties due to contamination, making it ineffective against E. coli and S. epidermidis. The findings highlight the potential of freeze-dried mucin extract and silicone adhesive films as innovative components for wound healing patches, emphasizing both their effectiveness in enhancing skin repair.